â€œColour Of Officeâ€: Restitutionary Redress Against Public Authority - Cornish, W.R. (Journal of Malaysian and Comparative Law, 2019)
An amended version of the first Sultan Azlan Shah Law Lecture of the Faculty of Law, University of Malaya delivered o April 23, 1986, in the presence of His Royal Highness, Sultan Azlan Shah, Sultan of Perak.